Faktor yang Mempengaruhi Kualitas Pelaporan Integrated Reporting pada Perusahaan Sektor Keuangan di Indonesia - Alexandra, Charlie; Sufiyati, Sufiyati (GEMA EKONOMI, 2023)
The integrated report is a complete report that contains the organization’s financial and non-financial information to communicate value to every shareholder. This study aims to examine the sharing factors affecting the quality of integrated reporting on financial companies listed in the Indonesia Stock Exchange during 2020-2022. Using a non-probability sampling technique with a purposive sampling method, 20 companies are obtained as samples or as many as 60 observed data. The data analysis method in this study was multiple linear regression using the SPSS Software version 25. The study found that leverage, as measured by Debt to Equity Ratio, has a significant positive effect, while firm age significantly negatively affects the quality of integrated reporting. Profitability and firm growth have a positive and insignificant effect. The firm size had a negative and insignificant effect on integrated reporting quality. For a better result, further research may explore another variable that influences integrated reporting quality.